(untitled) (Bulletin of the Department of Geology, 2008)
Landslides are the main natural hazards of the Kusma-Syangja area. The landslide hazard map (1:50,000 scale) of the region was prepared on the basis of aerial photo interpretation, extensive field survey of landforms, and analysis of geological, geomorphic, and hydrological processes. In the study area, flat-topped crests occur on phyllites and slates with gentle foliation. Steep and high rock cliffs prevail on counter dip slopes of quartzite, metasandstone, and dolomite. Karst topography is prominent in the carbonate terrain. Old river terraces are confined to the banks of the Kali Gandaki River, Modi Khola, Malyangdi Khola and Lamae Khola. Wedges slides and plane rockslides are the most common types of failure on rock slopes, whereas debrid slides, slumps and debris flows predominate on soil slopes. Large landslides occur at Khale, Armana, Gairiswanra, Kolpata, Ghaiyara, Karkineta, Arghaudi, Jharlangdi, Kharibhanjyang, in the lower reaches of the Andhi Khola, and on the Siddhartha Highway. They are observed on highly weathered and fracutred rocks, along fault zones, and on dip slopes. Frequently, the rock has three sets of discontinuities, which govern the failure pattern. Erosion and bank undercutting are common on the slopes adjacent to streams and gullies. There are several factors that directly or indirectly cause slopes instability. The change in slope gradient (owing to river undercutting, bank scouring by debris flow, or human acitivity), intercalactions of incompetent bands in relatively resistant rocks, presence of various sets of discontuinties as well as high uplift rates, heavy monsoon precipitation, and saturated slopes with groundwater are the major factors leading to slope failure. In the study area, the slopes with gradient ranging between 30 and 45 degrees are most vulnerable to instablilities. Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 9, 2002, pp. 61-76